Blog Development In Journalism Activities At Integrated Islamic Elementary School, Baitul Quran, Simalungun - Ahmad Salman Farid (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The use of blogs as a journalistic activity has not been carried out optimally by teachers or students. This is because many teachers do not know how and what steps to take in empowering blogs as learning media. The use of blogs as a forum for journalistic activities can be carried out at all school levels, especially elementary schools because students in general are used to accessing information through websites. On this opportunity for community service, the use of blogs is prioritized for SDIT Baitul Quran teachers in making school news accompanied by steps for making school news, loading news images and publishing them via blogs. This is done as an effort to promote school activities, excellent programs and the disclosure of school information in public spaces. Through this mentoring activity, teachers will know and understand how to create a blog account, change the theme to publish news as a journalistic process. It is hoped that the mentoring of learning practices using blogs will increase the positive image of the school, increase the number of students and the quality of education at SDIT Baitul Quran.